Identifikasi Ketebalan Tanah Gambut Menggunakan Metode Geolistrik Resistivitas Konfigurasi Wenner - Zulfian; Fiki Husnial Umam; Radhitya Perdhana (Progressive Physics Journal, 2025)
Peat soils are organic deposits that have a high carbon content. West Kalimantan is the second largest province in Kalimantan with a total peat ecosystem of around 1,729,980 Ha. In 2018, it was recorded that the peat area in West Kalimantan Province was 1,543,752 Ha. Its utilization in this province has increased every year although it has not yet reached a large area. Identification of peat thickness can be done with the resistivity geoelectric method. In this study, subsurface modeling was carried out using the Wenner configuration to determine the thickness of the peat layer. The modeling results are in the area of Perdana Street, Bansir Darat Village, Southeast Pontianak. The depth of the peat layer in the research area was found at a depth of 1.30 m to reach more than 5.5 m with a range of peat layer resistivity values obtained in the range of 131 Ωm - 267 Ωm. The clay layer is found at a depth of 1.31m - 8m. with a resistivity value range of 1.80 Ωm - 131 Ωm.